Nodular colloid degeneration of the skin: Differential diagnosis - Da?li, Adile Ferda; Özercan, Mehmet Reşat; Çiçek, Demet (Turkiye Klinikleri, 2009)
Colloid milium is a rare disorder characterized by translucent papules occurring on sun exposed areas of the body. Nodular colloid degeneration is a very rare type of colloid milium. A sixty-nine year old male patient engaged in farming presented to our hospital with facial lesions, which were itchy at times, and which had started 3 years ago and had increased thereafter. His dermatological examination revealed yellow, translucent, and gelatinous papules and plaques, with purplish foci, on the forehead and around both eyes. Biopsies were obtained with a presumptive diagnosis of systemic amyloidosis. Histopathological examination revealed nodular colloid degeneration. Lesions regressed after cryotherapy. Since colloid milium and nodular colloid degeneration, which is a type of it, are very rare and thus are not recognized until definitive diagnosis. Therefore, they should be considered in cases that have a long history of exposure to sun, and in the differential diagnosis of amyloidosis. Colloid milium is amenable to treatment with cryotherapy, dermabrasion, diathermia and long-pulsed Er: YAG laser. Copyright © 2009 by Türkiye Klinikleri.
Keywords: Metabolic; Pathology; Skin diseases